Prognostic value of gross tumor regression and plasma Epstein Barr Virus DNA levels at the end of intensity-modulated radiation therapy in patients with nasopharyngeal carcinoma. (March 2019) - Liang, Shao-Bo; Zhang, Ning; Chen, Dan-Ming; Yang, Xing-Li; Chen, Bin-Hong; Zhao, Hai; Lu, Rui-Liang; Chen, Yong; Fu, Li-Wu
Highlights: This study demonstrates gross tumor regression at the end of intensity-modulated radiation therapy (IMRT) has significant prognostic value for local and/or regional tumor control in patients with nasopharyngeal carcinoma (NPC). The patients with positive plasma EBV DNA at the end of IMRT are at higher risk of distant metastasis compared to the patients with negative plasma EBV DNA. Some timely and effective strengthening treatment might be administered to patients with persistent tumor or positive plasma EBV DNA at the end of IMRT. Abstract: Purpose: To assess gross tumor regression and plasma Epstein–Barr virus (EBV)-DNA levels at the end of intensity-modulated radiation therapy (IMRT) and its prognostic impact on patients with nasopharyngeal carcinoma (NPC). Participants and Methods: In total, 397 patients with non-metastatic, histologically confirmed NPC were retrospectively examined. All patients underwent magnetic resonance imaging of the nasopharynx and neck, and plasma EBV DNA assays before treatment and at the end of IMRT. Results: The estimated 5-year loco-regional, local and regional relapse-free survival rates for patients with complete response (CR) and non-CR of the total tumor, primary tumor and metastatic lymph nodes at the end of IMRT were 94.9% vs. 85.8%, 96.6% vs. 87.3%, and 98.7% vs. 89.8%, respectively ( P  < 0.05). The estimated 5-year loco-regional relapse-free survival (LRRFS) rates for patients with persistent tumor with and without boost irradiation were 95.3% vs. 83%, respectively ( P  = 0.034). The estimated 5-year overall survival (OS), failure-free survival (FFS) and distant metastasis-free survival (DMFS) rates for patients with negative and positive plasma EBV DNA at the end of IMRT were 83.1% vs. 50.3%, 81.5% vs. 49.3%, and 87.6% vs. 61.5%, respectively ( P  < 0.001). Multivariate analyses indicated that regression of the total tumor and boost irradiation was an independent predictor of LRRFS, and plasma EBV DNA levels were independent predictors of OS, FFS and DMFS. Conclusions: Gross tumor regression and plasma EBV DNA levels at the end of IMRT served as predictors of poor prognosis for patients with NPC. The patients with persistent tumor and/or positive plasma EBV DNA might require timely strengthening treatment.